Analyzing The Encountered Problems and Possible Solutions of Converting Relational Databases to Graph Databases - Ramazan Altın; A. Cumhur Kınacı (Journal of Advanced Research in Natural and Applied Sciences, 2022)
Relational database management systems have been used for storing data for a long time.However, these systems are insufficient to analyze the large and complex structure of the data. Graphdatabases are becoming more common day by day due to their capacity to contribute to the analysis.Also, graph databases are better at modeling and querying complex relationships than relationaldatabases. To use graph databases with old data stored in relational databases a transfer process isneeded. In this study, the problems to be encountered in transferring the data stored in a relationaldatabase to a graph database were examined and methods that could be used as solutions to themwere proposed. In addition, it is aimed to prevent data loss and data inconsistency that may occur withdesign errors in relational databases. For this purpose, the normalization process needs to be appliedto a relational database before transferring data to a graph database. In our study, we developed amethod that converts data to the first normal form during the transfer. But for better data consistency inpractice third normal form is the minimum requirement. By using the functional dependencies found,it is possible to make relational databases suitable for higher normal forms. For functional dependencydetection, which is normally a very time-consuming and costly process, we developed a method basedon a graph database.